THE ROLE OF SMALL BUSINESS ENTITIES IN THE PROGRAM "FROM POVERTY TO WELL-BEING" - Makhamadaliev, Boburbek; Yuldashev, Kadirjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Annotation. This article analyzes the work being carried out in the Republic of Uzbekistan to reduce poverty by supporting the activities of small businesses. In this regard, within the framework of the "From Poverty to Prosperity" program in our country, the formation of a poverty register, the identification of a targeted list of representatives of the poor population, the formation of individual plans for each family member based on a new approach to lifting families included in the poverty register out of poverty and ensuring the high-quality implementation of these plans, as well as in order to ensure the fulfillment of the tasks set forth in the Decree, measures and main directions for poverty reduction in the Namangan region, the results achieved in this system in the region, and foreign experience in poverty reduction are described.